2015
DOI: 10.1148/radiol.2015142470
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative US Features and Recurrence in Patients with Classic Papillary Thyroid Carcinoma

Abstract: The presence of malignant-appearing US features was independently associated with recurrence in patients with classic PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 40 publications
2
47
1
1
Order By: Relevance
“…After surgery, most patients need to be on treatment with thyroid hormone for the rest of their life. If the cancer is large and if it has spread to lymph nodes, treatment with radioactive iodine can be used after the thyroid gland removed [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After surgery, most patients need to be on treatment with thyroid hormone for the rest of their life. If the cancer is large and if it has spread to lymph nodes, treatment with radioactive iodine can be used after the thyroid gland removed [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid stiffness index obtained with E is useful in differentiating between malignant and benign thyroid nodules. It is possible measure tissue deformation in response to compression, what give us an idea of tissue stiffness [1,2].…”
mentioning
confidence: 99%
“…Previous investigators have found that malignant-appearing PTCs, i.e., PTCs that had at least one suspicious US feature, more frequently had aggressive prognostic factors than benign-appearing PTCs and that the presence of suspicious US features was independently associated with recurrence. [16,17] In one study, a greater number of suspicious US findings was associated with multifocality, extrathyroidal extension, lymph node metastasis, and a high stage. [16] Although the specific US features that are classified as suspicious by the TIRADS differ from the two prior studies, our results also support the potential role of US features as a prognostic tool in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] Recently, the thyroid imaging reporting and data system (TIRADS) by Kwak et al [18] which is based on the number of suspicious US features, has been shown to be accurate in malignancy risk stratification of thyroid nodules and simple to apply to clinical practice. However, its association with established prognostic factors in patients with PTC has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…All patients in this study had been included in the study population of a previously published article. 16) However, the previous study had different research purposes from our own and did not deal with the same concepts.…”
Section: Patientsmentioning
confidence: 93%